Factors that Master of Nursing students associate with study progress in higher education institutions in Gauteng province - Patricia Y. Mudzi; Priscilla M. Jiyane; Nombulelo Sepeng (AOSIS, 2022)
Background: Globally, the unsatisfactory progress of postgraduate students registered for a master's degree is a cause for concern. It affects graduation numbers and completion time. Aim: This study aimed to determine the perceived supervisory-researcher community support, research writing, work-life balance, and research conceptions factors that Master of Nursing students associate with study progress. Setting: The study was conducted in three selected higher education institutions (HEIs) in the Gauteng province. Method: A correlational cross-sectional research design was utilised. A self-administered questionnaire adapted from the Cross-Country Doctoral Experience Survey was e-mailed to a total sample of 136 Master of Nursing students who were at least in their second year of study, of which 122 (89.7%) responded. Descriptive statistics, factor analysis, the Mann-Whitney U test, and the Kruskal-Wallis test were used to analyse the responses. Results: Most of the students' perception was greater regarding supervisory-researcher community support and research conceptions. Despite a high mean composite score of 4.134 (SD-1.452) on work-life balance, some respondents found it difficult to balance work and life. Respondents with a source of income perceived greater supervisory-researcher community support (p = 0.022) while those studying full-time had better research writing perceptions (p = 0.002). Conclusion: There is need for HEIs to develop or strengthen interventions targeting research writing and work-life balance factors that were perceived to result in less support. Funding remains a concern for Master of Nursing students. Contribution: This study contributes to knowledge on factors that Master of Nursing students associated with study progress.